Particle physics experiments based on the AWAKE acceleration scheme. (12th August 2019) - Wing, M.
Abstract : New particle acceleration schemes open up exciting opportunities, potentially providing more compact or higher-energy accelerators. The AWAKE experiment at CERN is currently taking data to establish the method of proton-driven plasma wakefield acceleration. A second phase aims to demonstrate that bunches of about 10 9 electrons can be accelerated to high energy, preserving emittance and that the process is scalable with length. With this, an electron beam of O (50 GeV) could be available for new fixed-target or beam-dump experiments searching for the hidden sector, like dark photons. The rate of electrons on target could be increased by a factor of more than 1000 compared to that currently available, leading to a corresponding increase in sensitivity to new physics. Such a beam could also be brought into collision with a high-power laser and thereby probe the completely unmeasured region of strong fields at values of the Schwinger critical field. An ultimate goal is to produce an electron beam of O (3 TeV) and collide with an Large Hadron Collider proton beam. This very high-energy electron–proton collider would probe a new regime in which the structure of matter is completely unknown. This article is part of the Theo Murphy meeting issue 'Directions in particle beam-driven plasma wakefield acceleration'.